Regiões de risco, caracterização da antese em cereais de inverno e sista de alerta para giberela, em trigo - Zoldan, Sandra Maria (2008)
Scab or head blight (caused by Gibberela zeae (Schw.) Petch (anamorph = Fusarium graminearum Schwabe), has been pointed out as one of most important diseases of small grains, due to the occurrence of severe epidemic in the latter years. Disease is highly dependent of climatic conditions for its establishment as the major factor the rain frequency since the beginning of flowering to grain filling. Head blight causes yield damage and reduces grain quality by the production of micotoxins which may cause toxicological problems when contaminated kernels are consumed. Control through resistant cultivars is difficult to be obtained, and genetic resistance present in available cultivars are insufficient when climatic conditions are very favorable for disease onset. Although efficient fungicides are available to control the pathogen, there are problems related to the field application, as insufficient coverage of the susceptible plant organs, the caught anthers, what affects control efficiency. The actual problem is the increased disease incidence and the caused damage and the absence of safe control measures that guarantee to the growers the damage reduction. Hence the objectives of this work were: considering the climatic factors: temperature, air relative humidity and rainfall occurred in the major number of years with available meteorological data, to identify the wheat flowering dates in regions in southern Brazil which show lower risks for scab occurrence as a control measure in the disease management allowing generate risk maps which help to warn the growers and agronomists on disease favorability in one time and region. Identify morphological characteristics in the host plant which may be useful to help the breeding programs for scab resistance/tolerance: b) anthesis duration in small grains; c) relate disease onset with the presence of caught anthers; d) compare and assess the cultivars reaction to the disease, through the effect on yield traits; e) compare disease assessment methods; f) and to evaluate the effect of flowering time on disease occurrence; g) through spike wet duration, temperature and susceptible host stage interactions create and validate a warning system for wheat scab, identify the best time for spraying fungicides to improve control efficiency and economy. With the goal to identify heading time and favorable regions for wheat scab occurrence in Southern Brazil an equation developed by Moschini & Fortugno (1996), that identifies the climatic factors related to scab incidence in wheat spikes was used. It was calculated the Likelihood for Scab Infection (PIG) through the analysis of meteorological data from 13 counties in the states in southern Brazil: Júlio de Castilhos (25 years), Passo Fundo (31 years), Santa Rosa (17 years), São Borja (30 years), São Gabriel (28 years) e Vacaria (17/18 years), Campos Novos (30 years), Chapecó (26 years), Cascavel (15/16 years), Cianorte (29/30 years), Guarapuava (29 years), Londrina (30 years) and Palotina (31 years). The meteorological elements processed at a time segment beginning eight days before heading date (50% emerged heads) and ending when 30 days are completed. After calculating PIG for each county grouped by heading date (05/08; 15/08; 25/08; 05/09; 15/09; 25/09; 05/10; 15/10; 25/10; 05/11; 15/11; 25/11) frequency of scab occurrence were calculated. PIG was classified as low (0-25%), medium (>25-50%) and high (>50%) and risk maps generated by the mean of disease frequency for each date in two temperature intervals. Zones of risk maps are added useful tools to evaluate the climatic conditions favorable for wheat scab epidemics. They are also useful for decision making for the chemical control of above ground plant diseases. It may be concluded that the heading date of among 15/09 and 05/10 are the period of the highest risk, as well for Guarapuava region , where was detected in several heading times high PIG, should be monitored and cultural and chemical control measures implemented. Experiments were carried out in the Laboratório de Fitopatologia and in the experimental field of Faculdade de Agronomia and Medicina Veterinária of Universidade de Passo Fundo/RS during the winter seasons of 2005 (5 seeding times) and 2006 (4 seeding times). Results showed through correlation analysis that the final scab incidence, in the field, is related with the number of caught anthers per spike. In this work the importance of caught anthers in the infectious process was confirmed . Cultivar Pampeano and the line CEP 59 showed the lowest susceptibility disease index, while cultivar CD 114 the highest index. Among the pathometric methods used to assess scab intensity the best was through the disease index. In experiments conducted in growth chamber with wheat cultivar BR 23 scab susceptible, the interactions between five temperatures (10, 15, 20, 25 e 30°C) and eleven periods of head wetting (0, 5, 10, 15, 20, 25, 30, 35, 40, 45 e 50 hours) on scab intensity were assessed. Each temperature was assessed in an individual experiment an hour of wetting the treatments. Disease severity values superior to 90% were detected at 25oC with 50 hour of wetting. Even at 10ºC, minimum tested temperature, there was disease occurrence. Variation in wheat scab intensity by the temperature, were explained by the Beta generalized, and head wetting period by Gompertz model. Disease intensity was modeled in function of temperature and head wetting durations. The resulting equation showed a precise description of the scab intensity answer to the combined effects of temperature and wetting duration. The model was used to make tables of critical periods which were used to validate the warning model for what scab in field experiments. To validate the warning system for wheat and triticale, the Zoldan (2008) model and Reis & Blum (2204) were assessed and compared through the data of scab intensity in five wheat genotypes and one of triticale in 2005 growing season (five seeding times) and 2006 (six seeding times). From the date of flowering beginning and following the daily values of likelihood infection the sum was obtained for each model (SVDPI). It was concluded that the Reis & Blum (2004) was the best model and the SVDPI ≥ to 2 as the determinant value for warning disease occurrence and the need for control measures implementation. The system is proposed to be called UPF-Scab-alerta.